Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.3.rs-63438/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between the non-HDL-cholesterol to HDL-cholesterol ratio and non-alcoholic fatty liver disease in Chinese children and adolescents: a large single-center cross-sectional study

Abstract: Background: The non-HDL-cholesterol to HDL-cholesterol (NHDLC/HDLC) ratio is closely related to a variety of dyslipidemia-related diseases. This study aimed to inspect the relationship between the NHDLC/HDLC ratio and non-alcoholic fatty liver (NAFLD) in children and adolescents.Methods: In this cross-sectional survey, a total of 7,759 eligible Chinese children and adolescents (5,692 boys and 2,067 girls) received routine medical examinations. The anthropometric and laboratory data of the subjects were collect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Regarding the association between UHR and ALT, Mehmet Ali Kosekli et al observed that UHR was positively associated with ALT through a controlled study [24]. Moreover, a positive association between UHR and ALT was also reported in Chinese lean individuals by Ya-Nan Zhang et al [29]. These results are consistent with the ndings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the association between UHR and ALT, Mehmet Ali Kosekli et al observed that UHR was positively associated with ALT through a controlled study [24]. Moreover, a positive association between UHR and ALT was also reported in Chinese lean individuals by Ya-Nan Zhang et al [29]. These results are consistent with the ndings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…The search identified 735 references and 127 papers were selected for full‐text review. Finally, 31 articles 14‐44 describing 33 study populations fulfilled the criteria and included in the systematic review and pooled analysis (Figure 1). All the articles were published after 2004, and before April 28, 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The features of the 31 studies 14‐44 were provided in Table 1. Eighteen studies in Eastern Asia (15 from China, two from Japan, one from Korea), 11 studies in Western Asia (five from Iran, five from Turkey, one from Israel) and two studies in Southern Asia (two from India).…”
Section: Resultsmentioning
confidence: 99%
“…Alkassabany et al, 2014 (15) 7.4% 1.10 [0.21, 5.87] Ayonrinde et al, 2011 (16) 6.0% 0.08 [0.01, 0.58] Yu et al, 2019 (17) 8.5% 0.07 [0.02, 0.31] Ezaizi et al, 2019 (18) 6.1% 0.04 [0.00, 0.26] Gupta et al, 2011 (19) 8.3% 0.13 [0.03, 0.57] Jimenez-Rivera et al, 2017 (20) 5.7% 0.01 [0.00, 0.07] Kang et al, 2018 (21) 5.7% 0.17 [0.02, 1.38] Malespin et al, 2015 (22) 5.7% 0.16 [0.02, 1.37] Mohamed et al, 2020 (23) 6.0% 0.01 [0.00, 0.11] Park et al, 2020 (24) 5.9% 0.09 [0.01, 0.70] Peña-Vélez et al, 2020 (25) 6.1% 0.01 [0.00, 0.06] Sae-Wong et al, 2021 (26) 5.8% 0.08 [0.01, 0.67] Conjeevaram Selvakumar et al, 2018 (27) 5.8% 0.12 [0.02, 1.00] Song et al, 2017 (28) 5.9% 0.11 [0.01, 0.87] Yang et al, 2020 (29) 5.5% 0.25 [0.03, 2.24] Zhang et al, 2015 (30) 5.6% 0. (15) Egypt 800 ALT Ayonrinde et al, 2011 (16) Australia 1,170 Ultrasound Yu et al, 2019 (17) United States 408 MRI and ALT Ezaizi et al, 2019 (18) United States 344 ALT Gupta et al, 2011 (19) United States 655 ALT Jimenez-Rivera et al, 2017 (20) Canada 97 Ultrasound and biochemical method Kang et al, 2018 (21) Korea 1,416 ALT Malespin et al, 2015 (22) United States 407 ALT Mohamed et al, 2020 (23) Malaysia 33 Ultrasound Park et al, 2020 (24) Korea 4,448 ALT Peña-Vélez et al, 2020 (25) Mexico 112 Ultrasound Sae-Wong et al, 2021 (26) Thailand 50 ALT Conjeevaram Selvakumar et al, 2018 (27) United States 1,482 ALT Song et al, 2017 (28) China 831 ALT Yang et al, 2020 (29) China 7,759 Ultrasound Zhang et al, 2015 (30) China 7,229 Ultrasound ALT -alanine transaminase; MRI -magnetic resonance imaging.…”
Section: Study Of Subgroup Weight Odds Ratio M-h Random 95% Confidenc...mentioning
confidence: 99%